In vitro IN VITRO EVALUATION OF THE ANTIBACTERIAL EFFICACY OF DATURA STRAMONIUM LEAF AGAINST HELICOBACTER PYLORI - Ajadi, Ayobami E.; Ajijolakewu, A. K.; Ayoola, S. A.; Omotunde, M. Y.; Aguda, B. A. (FUDMA Journal of Sciences, 2024)
The rise in antimicrobial resistance has spurred the search for plant-based alternatives due to their therapeutic properties. This study evaluates the in vitro efficacies of Datura stramonium leaves extracts against Helicobacter pylori. Leaves were extracted using selected polar and non-polar solvents, and antibacterial activity were assessed through the agar well diffusion method at varying concentrations with H.pylori as test bacteria. Phytochemical analysis was conducted using standard methods. Results showed that at 500 mg/ml, ethanolic extracts of Datura stramonium showed the highest zone of inhibition (22.02 ± 0.02 mm), followed by n-Hexane (17.03 ± 0.03 mm) and aqueous extracts (15.03 ± 0.03 mm). Ethanolic and n-Hexane of Datura stramonium extracts had high MIC values (125 mg/ml), while the aqueous extract had 250 mg/ml. Ethanolic extract and n-Hexane extracts of Datura stramonium also had bactericidal activity at 500 mg/ml, unlike the aqueous extracts. Phytochemical analysis revealed the presence glycosides (74.4± 0.04) mg/ml, phenols (131.8±0.03) mg/ml, alkaloids (100.5±0.00) mg/ml flavonoids (2.6±0.02) mg/ml, tannins (124.2±0.02) mg/ml, saponins (14.1±0.02) mg/ml, triterpenoids (37.9±0.00) mg/ml, and steroids (31.9±0.01) mg/ml in the extracts. The results showed that Datura stramonium leaf ethanolic extracts had strong antibacterial activity against H. pylori, suggesting that they could be used as an alternative to conventional therapies for H. pylori infections.
Keywords: Antimicrobial resistance; Antibacterial activity; Datura stramonium; Helicobacter pylori